2019
DOI: 10.24171/j.phrp.2019.10.6.06
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Relationship Between Self-Efficacy, General Health and Burnout Among Iranian Health Workers

Abstract: ObjectivesTo evaluate the relationship between self-efficacy, general health and burnout of the staff at Shahroud University of Medical Sciences.MethodsIn 2015, 249 staff at Shahroud University of Medical Sciences (from a total reference population of 520 staff members) were selected through stratified random sampling. To collect the data, Sherer self-efficacy Scale, General Health Questionnaire and Maslach Burnout Inventory were used. The collected data were analyzed through ANOVA, Pearson correlation and Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 25 publications
1
9
1
Order By: Relevance
“… 25 30 31 Research on healthcare workers has also found a significant relationship between self-efficacy and burn-out. 32 Healthcare workers with better self-efficacy reported higher job satisfaction. They were more likely to mobilise new resources when faced with difficulties and obstacles, such as seeking help from colleagues and supervisors.…”
Section: Discussionmentioning
confidence: 98%
“… 25 30 31 Research on healthcare workers has also found a significant relationship between self-efficacy and burn-out. 32 Healthcare workers with better self-efficacy reported higher job satisfaction. They were more likely to mobilise new resources when faced with difficulties and obstacles, such as seeking help from colleagues and supervisors.…”
Section: Discussionmentioning
confidence: 98%
“…A previous study used network analysis to explore the network structure of MW in four UK cohorts, and also found strong associations between MW8 and MW10 as well as between MW6 and MW7 ( 29 ). Take MW1–MW2, for example, optimism about the future may be the embodiment of ability and associated with increased confidence ( 54 , 55 ). Therefore, when a person is optimistic about his/her future, he/she may find himself/herself useful.…”
Section: Discussionmentioning
confidence: 99%
“…Manipulating self-efficacy is an important way to prevent mental health problems when dealing with stress ( Schönfeld et al, 2019 ). Previous studies have focused on the effects of self-efficacy on the mental health and work quality of medical staff ( Amiri et al, 2019 ; Tang et al, 2019 ), and it suggested that necessary interventions should be implemented to improve the self-efficacy of medical staff. In the prevention and control of COVID-19, medical staff is faced with two main difficulties.…”
Section: Discussionmentioning
confidence: 99%